Unsteady Pressure Pulsations in Pumps—A Review - Zhang, Ning; Li, Delin; Gao, Bo; Ni, Dan; Li, Zhong (Energies (Basel), 2023)
Unsteady pressure-pulsation-induced severe vibration and high alternating stress can cause some unexpected results, including impeller crack and structural damage of the entire pumping system. In the present paper, a review on pressure pulsations in pumps is carried out based on the published studies. A comprehensive view on pressure pulsations from several aspects is discussed in detail. The contents of the studies include the mechanism of rotor–stator interaction; a prediction model and experimental and numerical investigations of pressure pulsations; unsteady rotating-stall-induced pressure pulsations at off-design flow rates; the relationship between pressure pulsation and the internal flow structure and cavitation; and the reduction in pressure pulsation caused by some effective approaches. It is concluded that unsteady pressure pulsation in pumps is closely associated with complex flow structures, for instance flow separation, cavitation, and rotating stall. The rotor–stator interaction mainly dominates pressure pulsation characterized by the discrete components in pressure spectrum. To reduce pressure pulsation, some effective approaches are proposed, such as increasing the rotor–stator gap, staggered blade, and blade modification. Finally, several suggestions for future works are given and discussed considering the current research. The review contributes to better understanding of pressure pulsations in centrifugal pumps, and may also benefit engineers in controlling pressure pulsations in some fields, such as pumps in nuclear reactor.